Thieme Chemistry Journals Awardees – Where Are They Now?Molybdenum(V)-Mediated Synthesis of Nonsymmetric Diaryl and Aryl Alkyl Chalcogenides - Franzmann, Peter; Beil, Sebastian B.; Winterscheid, Peter M.; Schollmeyer, Dieter; Waldvogel, Siegfried R. (Synlett, 2017)
Oxidative chalcogenation reaction using molybdenum(V) reagents provides fast access to a wide range of nonsymmetric aryl sulfides and selenides. The established protocol is tolerated by a variety of labile functions, protecting groups, and aromatic heterocycles. In particular, when labile moieties are present, the use of molybdenum(V) reagents provides superior yields compared to other oxidants.
Keywords: molybdenum pentachloride; oxidative coupling; C–S bond formation; cross-coupling; disulfides